1997
DOI: 10.1523/jneurosci.17-12-04642.1997
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-R Is an Intrinsic Autocrine Factor for Oligodendrocyte Differentiation and Promotes Cell Adhesion by a SulfatideMediated Mechanism

Abstract: O4ϩ oligodendrocyte (OL) progenitors in the mammalian CNS are committed fully to terminal differentiation into myelinforming cells. In the absence of other cell types in vitro, OL differentiation reproduces the in vivo development with a correct timing, suggesting the existence of an intrinsic regulatory mechanism that presently is unknown. We have examined the effect of two isoforms of the extracellular matrix (ECM) molecule tenascin-R ( TN-R), which is expressed by OLs during the process of myelination, on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 86 publications
4
82
0
1
Order By: Relevance
“…However, the finding that both sulfatide and GM1 are substrates of MRP1 might still be of distinct interest. Sulfatide has been linked to several processes like neuronal development (41), the modulation of blood coagulation (42), and tumor cell metastasis (43). As the MRP1 protein is expressed ubiquitously throughout the body and can be expressed on chemotherapy-resistant tumors, MRP1-mediated transport of sulfatide may well play a role in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding that both sulfatide and GM1 are substrates of MRP1 might still be of distinct interest. Sulfatide has been linked to several processes like neuronal development (41), the modulation of blood coagulation (42), and tumor cell metastasis (43). As the MRP1 protein is expressed ubiquitously throughout the body and can be expressed on chemotherapy-resistant tumors, MRP1-mediated transport of sulfatide may well play a role in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, sulfatide carries a negative charge and can therefore bind to positively charged proteins by electrostatic forces, a characteristic that may account for the large number of sulfatide -protein interactions (for review, see Vos et al, 1994). Of particular interest is a well documented role for sulfatide, but not for GalC, in adhesion with extracellular matrix molecules, such as tenascin-R/janusin/J-1, laminin, and thrombospondin (Roberts and Ginsburg, 1988;Pesheva et al, 1997), that are present in the CNS (McLoon et al, 1988;O'Shea et al, 1990;Bartsch et al, 1992) and are secreted by the OLs and/or astrocytes in culture (Oh and Yong, 1996;Pesheva et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, integrin-mediated inhibition of OL differentiation (similar to that induced by anti-galactolipids) occurs in OL cultures treated with RGD peptide, a sequence in the EC M molecules recognized by the integrins (Cardwell and Rome, 1988;Malek-Hedayat and Rome, 1994). Similarly tenascin-R, which is secreted by OLs in culture (Pesheva et al, 1997), binds to both sulfatide and F3/F11/ contactin (Nörenberg et al, 1995) on the OL surface (Koch et al, 1997;Pesheva et al, 1997). F3 intern binds to Fyn, a nonreceptor tyrosine kinase that is implicated as an important signaling molecule in OL development and myelin formation (Osterhout et al, 1999;Umemori et al, 1999).…”
mentioning
confidence: 99%
“…Because the hydroxy FAs originate from myelinating oligodendrocytes in gray matter, sulfatide with the hydroxy FAs is suggested to infl uence myelin stability ( 26 ). On the other hand, the myelin formation of cultured Schwann cells appears to be initiated by sulfatide through its binding to extracellular matrixes, like tenascin-R or laminin, which binds to integrins (signaling molecules) and can stimulate c-Src/Fyn kinase (27)(28)(29). Histological analysis showed that axons of the optic nerve in CST-defi cient mice were well-myelinated.…”
Section: Nervous Systemmentioning
confidence: 99%